Knockdown of the cochaperone SGTA results in the suppression of androgen and PI3K/Akt signaling and inhibition of prostate cancer cell proliferation. Issue 12 (6th July 2013) - Trotta, Andrew P.; Need, Eleanor F.; Selth, Luke A.; Chopra, Samarth; Pinnock, Carole B.; Leach, Damien A.; Coetzee, Gerhard A.; Butler, Lisa M.; Tilley, Wayne D.; Buchanan, Grant
<x xml:space="preserve">Abstract</x> Solid tumors have an increased reliance on Hsp70/Hsp90 molecular chaperones for proliferation, survival and maintenance of intracellular signaling systems. An underinvestigated component of the chaperone system is the tetratricopeptide repeat (TPR)‐containing cochaperone, which coordinates Hsp70/Hsp90 involvement on client proteins as well as having diverse individual actions. A potentially important cochaperone in prostate cancer (PCa) is small glutamine‐rich TPR‐containing protein alpha (SGTA), which interacts with the androgen receptor (AR) and other critical cancer‐related client proteins. In this study, the authors used small interfering RNA coupled with genome‐wide expression profiling to investigate the biological significance of SGTA in PCa and its influence on AR signaling. Knockdown of SGTA for 72 hr in PCa C4‐2B cells significantly altered expression of >1, 900 genes (58% decreased) and reduced cell proliferation (p < 0.05). The regulation of 35% of 5α‐dihydrotestosterone (DHT) target genes was affected by SGTA knockdown, with gene‐specific effects on basal or DHT‐induced expression or both. Pathway analysis revealed a role for SGTA in p53, generic PCa and phosphoinositol kinase (PI3K) signaling pathways; the latter evident by a reduction in PI3K subunit p100β levels and decreased phosphorylated Akt. Immunohistochemical analysis of 64 primary advanced PCa samples showed a significant increase in the AR:SGTA ratio in cancerous lesions compared to patient‐matched benign prostatic hyperplasia tissue (p < 0.02). This study not only provides insight into the biological actions of SGTA and its effect on genome‐wide AR transcriptional activity and other therapeutically targeted intracellular signaling pathways but also provides evidence for PCa‐specific alterations in SGTA expression.